2019
DOI: 10.1016/j.ihj.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of familial hypercholesterolemia in premature coronary artery disease patients admitted to a tertiary care hospital in North India

Abstract: Aims The prevalence of premature coronary artery disease (CAD) in India is two to three times more than other ethnic groups. Untreated heterozygous familial hypercholesterolemia (FH) is one of the important causes for premature CAD. As the age advances, these patients without treatment have 100 times increased risk of cardiovascular (CV) mortality resulting from myocardial infarction (MI). Recent evidence suggests that one in 250 individuals may be affected by FH (nearly 40 million people globally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
(25 reference statements)
2
12
1
Order By: Relevance
“…In our study, no patient had tendinous xanthomatosis while 3 patients had Arcus cornialis. In contrast to our study, Sawhney et al, stated that 8.35% had arcus cornialis and 0.16% of patients had tendinous xanthomatosis, this may be high main age in our study [21]. Regarding Correlation between Dutch score and other variables in our study there was a significant negative correlation between Dutch score and age p = 0.021, while there was a highly positive correlation with total cholesterol and LDL p < 0.001.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, no patient had tendinous xanthomatosis while 3 patients had Arcus cornialis. In contrast to our study, Sawhney et al, stated that 8.35% had arcus cornialis and 0.16% of patients had tendinous xanthomatosis, this may be high main age in our study [21]. Regarding Correlation between Dutch score and other variables in our study there was a significant negative correlation between Dutch score and age p = 0.021, while there was a highly positive correlation with total cholesterol and LDL p < 0.001.…”
Section: Discussioncontrasting
confidence: 99%
“…Familial hypercholesterolemia is one of the most common genetic disorders of lipid metabolism, which is an underdiagnosed, undertreated cause of premature coronary heart disease. Results from a previous study showed that in India, 15% of the patients who had myocardial infarction at a young age also had familial hypercholesterolemia, 3 and similar studies showed a 10% prevalence of familial hypercholesterolemia in the USA and a 14•7% prevalence of the condition in Australia. 4,5 Once an individual is diagnosed with familial hypercholesterolemia, other family members should be identified by cascade screening by clinical history and lipid profiling rather than genetic testing, which is neither easily available nor affordable.…”
Section: Family-based Approach In Cardiovascular Risk Reductionmentioning
confidence: 78%
“…The performance of the assay was verified by comparison of results with Sanger DNA sequencing testing was 4.4% and definite/probable FH diagnosed by the modified Dutch Lipid Clinic Network (DLCN) criteria was 23.6%. Investigators from New Delhi, India, assessed individuals with premature CAD for FH using the DLCN criteria 18) . Four percent were diagnosed as definite and 11% as probable.…”
Section: Genetics Of Fh In Asia Pacificmentioning
confidence: 99%
“…In addition to the publications from China 17) , India 18) , and Japan 19) described in the epidemiology section of this review, Table 5 provides the summaries of additional efforts to screen ACS patients in the Asia Pacific region.…”
Section: Screening Of Individuals With Acsmentioning
confidence: 99%